Study of the dynamic vertical interaction of multi-axle rolling stock with railway track - Abdullayeva, Asel; Toktamyssov, Aidos; Bakyt, Gabit; Aikumbekov, Muslim; Yelshibekov, Amandyk; Abylkhanova, Ayaulym (Sound & Vibration, 2026)
The continuous growth in the demand for increased capacity of the existing railway network of the Republic of Kazakhstan, particularly in regions bordering the Russian Federation and China, makes the issue of improving the operational safety of heavy-haul freight trains with increased mass and length especially relevant. The introduction of heavy trains represents a complex engineering and operational task that involves the use of more powerful locomotives, increased axle loads, reconstruction of track infrastructure and power supply systems, and the improvement of transportation technologies. In addition, higher train speeds combined with increasing freight traffic intensity require improvements in the strength and stability of the railway track structure. The technical policy of Kazakhstan Temir Zholy is aimed at a full transition to continuously welded track constructed on reinforced-concrete foundations. Edge stresses arising from rail bending and torsion under vertical and horizontal loads from rolling stock are among the key parameters determining rail strength. It is well known that the half-sum of the edge stresses characterizes the vertical impact on the track, whereas their half-difference represents the horizontal impact (lateral force). These parameters also reflect the influence of force moments generated by lateral loads and by the displacement of the conventional center of the wheel-rail contact patch relative to the rail head.